(3BOGH Sdhc GdNhGUs - (3jhSa Hf Ydj Hf CMeO Hf GdHbGd,J (B668 (3g` s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdMeO ddg GdYXje TCfg CeG HYO abO CdaJ gPG GdJCdja ai ecI TQagG Gddg JYGdi Ke ESJOQcJg HeOjfI OeTb hROJ ajg ahGFO MJi EPG WGdYg GdeQjO GdUGOb s
(3BNQgG (B:s
(3hfNJe GdcJGH HgPg GdBjI GdcQjeI (B( (3CaQCjJ Ef eJYfGge Sfjf Ke LGAge eG cGfhG jhYOhf eG CZfi Yfge eG cGfhG jeJYhf (B) (3, hSde JSdjekG cKjQkG Edi jhe GdOjf JeJ GdQSGdI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B9 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B317 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B555s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs